The pathophysiology of severe falciparum malaria. - Phillips, R; Warrell, D (1986)
By the end of the 1940s, the clinical and pathological features of severe falciparum malaria had been well described by military physicians and pathologists working in theatres of war where the disease was endemic. From that time serious efforts were made to discover the pathophysiology of the severe manifestations of malaria because an understanding of these mechanisms forms an important basis for the clinical management of affected patients. Recently, after a period of neglect, there has been a revival of interest in malaria as a subject for clinical and laboratory research. In this article, Rodney Phillips and David Warrell review aspects of that work and attempt to unravel the mysteries of the pathophysiology of severe malaria in man.